STRATEGI PENCEGAHAN KECURANGAN (FRAUD) DALAM PENGELOLAAN KEUANGAN PEMERINTAH MENGGUNAKAN ANALYTICAL HIERARCHY PROCESS - Kurniasari, Novia Tri; Fariyanti, Anna; Ristiyanto, Nirwan (Jurnal Manajemen Pembangunan Daerah, 2018)
Fraud phenomenon involves many actors from the government sector. Fraudulent practices in government has a negative impact on the economic and social sectors. Therefore, need for prevention effort to avoid state’s material and non material losses. The objectives of this study were to formulate fraud prevention strategies by using Analytical Hierarchy Process. Sources of data used in this study were questionnaires and interviews to 5 expert respondent. Strategies for fraud prevention on government financial management: (1) improving the supervision and control system, (2) improving the organizational culture, (3) formulating anti fraud value in the organization, (4) implementing reward system and punisment firmly, (5) anti fraud socialization for employees, and (6) forming agent of change. Key words: fraud prevention, internal control system, organizational culture, anti fraud value, Analytical Hierarchy Process